Epifaniusza z Salaminy polemika z herezjami angelologicznymi - Drzyżdżyk, Szymon; Gilski, Marek (Vox Patrum, 2023)
The article presents the polemic of Epiphanius of Salamis with angelological heresies. Its purpose is therefore not only to present errors but is also an apology of correct faith. The article consists of four parts: the first concerns the existence of angels, the second focuses on their origins, the third deals with the question of their operation, and the fourth analyzes the role of angels in the afterlife of man. The most important conclusions from the analysis include: 1. Angelology was of interest not only in pre-Christian heresies (derived from Judaism) but also in heresies that emerged from Christianity. However, this topic does not appear when discussing the Greek schools of philosophy. 2. The author of Panarion does not always clearly present errors related to angelology. He himself points out that it was often not easy for him to precisely indicate the nature of a given heresy. 3. Epiphanius criticizes the angelological heresies on the basis of biblical and rational arguments, undermining their sources and reducing some theses to absurdity. He also uses the argument from authority, referring to the fathers (Clement, Irenaeus, Hippolytus).